Halal Certification Assistance for MSMEs in Facing the 2024 Halal Mandatory in Bojonegoro Regency East Java: Pendampingan Sertifikasi Halal Untuk UMKM Dalam Rangka Menghadapi Mandatory Halal Tahun 2024 Di Kabupaten Bojonegoro Jawa Timur - Effasa, Ahmad Saifurriza; Mazidah, Nurul; Rochmayanti, Dewi (Yayasan Ahmar Cendekia Indonesia, 2023)
This community service activity is carried out together with the MSME community who are members of the Creative Economy Center, Bojonegoro regency, East Java. With the aim of improving product quality and product competitiveness through halal certification assistance as an effort to face mandatory halal in 2024. The method carried out consists of several stages, First; Preparation, Identification and Survey, Second; Socialization and Education, Third; Assistance in Certification Management, four; Evaluation and Sustainability. The result of this activity was successful in increasing the understanding and awareness of the community and MSMEs about the importance of halal certification and from participants stated that they better understood the process and benefits of certification and the effectiveness of the programs carried out had been achieved and fulfilled than expected. Abstrak Kegiatan pengabdian kepada masyarakat ini dilaksanakan bersama dengan komunitas UMKM yang tergabung dalam Creative Economy Center kabupaten Bojonegoro Jawa Timur. Dengan tujuan meningkatkan kualitas produk dan daya saing produk melalui pendampingan sertifikasi halal sebagai upaya menghadapi mandatory halal tahun 2024. Metode yang dilakukan terdiri dari beberapa tahapan, Pertama; Persiapan, Identifikasi dan Survei, Kedua; Sosialisasi dan Edukasi, Ketiga; Pendampingan Pengurusan Sertifikasi, kempat; Evaluasi dan Keberlanjutan. Hasil dari kegiatan ini adalah berhasil meningkatkan pemahaman dan kesadaran masyarakat serta UMKM tentang pentingnya sertifikasi halal serta dari peserta menyatakan bahwa mereka lebih memahami proses dan manfaat sertifikasi serta efektivitas program yang dijalankan telah tercapai dan memenuhi dari yang diharapkan.